Production of flexible nanocomposite membranes for x-ray detectors - Ahmad I. Ayesh (10188469) (2020)
Flexible membranes of poly(vinyl alcohol) (PVA) polymer and CuO nanoparticles for x-ray detection applications are reported in this work. PVA represents a polymer matrix for nanoparticles, and its flexibility and electrical conductivity are enhanced by addition of glycerol (GL) plasticizer. Nanoparticles of an average size of 6.3 ∓ 2.4nm are produced by a solvothermal method and added to the PVA + GL solution with different concentrations. The flexible membranes are fabricated by solution casting on glass substrates. The effect of blending of PVA + GL with nanoparticles on different characteristics of the membranes including the flexibility as well as the melting, glass transition, and degradation temperatures are tested by differential scanning calorimetry, thermal gravimetric analysis, as well as both Raman and Fourier-transform infrared spectroscopy. Electrical impedance tests reveal that both dc resistance and activation energy decrease with increasing temperature as well as nanoparticle concentration. The produced membranes reveal electrical response to x-ray due to the presence of CuO nanoparticles, and this response rises with x-ray generator voltage. The results presented in this study specify that the produced membranes are easy to produce with low cost, thus, they represent potential candidates for practical applications including x-ray detection. Other Information Published in: Applied Surface Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.apsusc.2020.146958